2022
DOI: 10.3390/ma15155121
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Constituents and Mechanical Properties of Low-Density Fe-Cr-Ni-Mn-Al-C Stainless Steels

Abstract: Metallic material concepts associated with the sustainable and efficient use of resources are currently the subject of intensive research. Al addition to steel offers advantages in view of lightweight, durability, and efficient use of high-Fe scrap from the Al industry. In the present work, Al was added to Fe-12Cr-(9,12)Ni-3Mn-0.3C-xAl (x = 0.1–6) (wt.%) stainless steels to assess its influence on microstructure and mechanical properties. According to density measurements based on Archimedes’ principle, densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Because of this feature, they may be used in a variety of industries where weight reduction is desired, including the transportation, automotive, and aerospace sectors. It is also well known that these phases exhibit signi cant corrosion resistance, particularly under certain circumstances such as industrial atmospheres and seawater [29,30]. This makes them suitable for applications where corrosion resistance is essential, such as chemical reactions, outdoor buildings, and naval constructions [31].…”
Section: Sem/eds Resultsmentioning
confidence: 99%
“…Because of this feature, they may be used in a variety of industries where weight reduction is desired, including the transportation, automotive, and aerospace sectors. It is also well known that these phases exhibit signi cant corrosion resistance, particularly under certain circumstances such as industrial atmospheres and seawater [29,30]. This makes them suitable for applications where corrosion resistance is essential, such as chemical reactions, outdoor buildings, and naval constructions [31].…”
Section: Sem/eds Resultsmentioning
confidence: 99%
“…A study by Scherbring et al [15] reported that austenite and ferrite are two important phases can that can improve the strength of a duplex stainless steel. In other word, yield strength and hardness is increased in duplex stainless steel in the presence of ferrite constituents even when compared to the austenite.…”
Section: Types Of Microstructural Constituents In Steelsmentioning
confidence: 99%